Nanoencapsulation of Food Bioactive Ingredients : Principles and Applications. - Jafari, Seid Mahdi (Elsevier Science, 2017)
Nanoencapsulation of Food Bioactive Ingredients: Principles and Applications brings different nanoencapsulated food bioactive ingredients, their structure, applications, preparation, formulations and encapsulation methodologies, covering a wide range of compounds and giving detailed examples of the issues faced in their nano-encapsulation. The book addresses findings related to the study of natural food colorants, vitamins, antimicrobial agents, phenolic compounds, antioxidants, flavors, essential oils, fish oil and essential fatty acids, and other related ingredients. As a definitive manual for researchers and industry personnel working, or interested in, various branches of encapsulation for food ingredients and nutraceutical purposes, users will find this a great reference - Resumé vydavatele
1.7.1.2.3 Combination Technologies.
Keywords: balení potravin; potravinářská aditiva; biologicky aktivní látky; food packaging; food additives; bioactive compounds; mikroenkapsulace; monografie; elektronické knihy; monographs; electronic books